High frequency distributed temperature sensing and eddy covariance data observed at Sodankylä measurement station during summer/winter 2020 - Peltola, Olli (Zenodo, 2022)
This record contains high frequency distributed temperature sensing and eddy covariance data observed at Sodankylä measurement station and used in the following study: Peltola, O., Aurela, M., Launiainen, S. and Katul, G. (2022), Probing the eddy size and its effective mixing length in stably stratified roughness sublayer flows. Q J R Meteorol Soc. Accepted Author Manuscript. https://doi.org/10.1002/qj.4386 Sodankyla_DTS_mm_yyyy.zip These zip-files contain continuous high frequency potential temperature profiles measured along the Sodankylä 48-metre tall mast. See more information on the data in the netCDF-file attributes and on the measurement setup in the related scientific article. ECa.zip This zip-file contains high frequency data from an eddy covariance measurement setup located at 24.5 m height in the measurement height. See more information in ECa_readme.txt and on the measurement setup in the related scientific article. ECb.zip This zip-file contains high frequency data from an eddy covariance measurement setup located at 3 m height in the measurement height. See more information in ECb_readme.txt and on the measurement setup in the related scientific article. codes_Sodankyla.zip Matlab codes to produce similar figure as Fig. 2 in the abovementioned article, but for Sodankylä.